Consumers' Willingness to Consume Insect-Based Protein Depends on Descriptive Social Norms - Berger, Sebastian; Wyss, Annika M. (Frontiers in Sustainable Food Systems, 2020)
Eating of insects has been discussed as a more sustainable source of animal protein, but consumer research about uptake behavior of Western consumers is still scarce. Based on previous psychological research highlighting the role of social norms, the present research shows that even subtle cues about descriptive social norms affect Westerners’ willingness to eat unprocessed insects. In a series of four studies, we demonstrate that adherence to descriptive social norms underlies eating intention and behavior. Study 1 shows that individual beliefs about the descriptive social norm correlates with the willingness to eat an unprocessed insect, an effect which is replicated in an experiment showing the causal direction from norm beliefs to eating behavior (Study 2). Study 3 establishes that even in the absence of concrete information about social norms, consumers construe norms based on other options. Manipulating the perceived eating-contingent financial rewards for other people from the same population, un-incentivized participants are more readily willing to eat when they believe that others receive a higher incentive, an effect that is mediated by beliefs about the eating frequency of these participants. Study 4, finally, shows that manipulating beliefs about the norms provides the causal explanation as the effect of the incentive disappears when norm information is explicitly given. Taken together, the studies show that descriptive social norms partially underlie Westerns willingness (or reluctance) to consume insects and that behavioral change initiative could focus on the importance of using norms to increase reliance on non-standard sources of animal protein.